2019
DOI: 10.34050/els-jish.v2i4.8413
|View full text |Cite
|
Sign up to set email alerts
|

English Vowels and Diphthongs Problems of Sundanese Learners

Abstract: EFL Sundanese learners encounter the difficulties in English pronunciation. The learners are often unable to differ between English vowel sounds long [i:] with short [I] like the word cheese they pronounce it as /ʧIz/ instead of  /ʧiːz/, despite they have learned English since elementary school, officially they have learned English for around 5 years. The purpose of this study is to explore the interference of mother tongue in pronunciation field that was made by Sundanese learners dealing with English vowels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A pronunciation test consisting of 12 words containing the prepared categories of monophthongs and diphthongs were handed to the 30 participants. These words were adapted from the list of mispronounced words by participants in previous studies to ensure its reliability and validity (Kho, 2011;Priscilla Shak, 2016;Puspita, 2017;Nur Syahida & Zairil, 2017;Setyaningsih et al, 2019). The participants were instructed to record their pronunciation of each word three times using WhatsApp voice recording in order to ensure accurate pronunciation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pronunciation test consisting of 12 words containing the prepared categories of monophthongs and diphthongs were handed to the 30 participants. These words were adapted from the list of mispronounced words by participants in previous studies to ensure its reliability and validity (Kho, 2011;Priscilla Shak, 2016;Puspita, 2017;Nur Syahida & Zairil, 2017;Setyaningsih et al, 2019). The participants were instructed to record their pronunciation of each word three times using WhatsApp voice recording in order to ensure accurate pronunciation.…”
Section: Methodsmentioning
confidence: 99%
“…Kho (2011) discovered that Malaysians have difficulty distinguishing between ɪ/ and /i:/ or /ʊ/ and /u:/. In a research by Setyaningsih et al, (2019), non-native speakers were unable to distinguish between long vowel /i:/ and short vowel /ɪ/, pronouncing the word cheese as /ʧɪz/ rather than /ʧiːz/. Pronunciation errors involving diphthongs are also common in MalE.…”
Section: Mispronunciation Of English Vowelmentioning
confidence: 99%
See 1 more Smart Citation
“…By diphthong, phoneticians mean the combination of two vowels in the same syllable. Quoting Jones, Cohen said that there are nine diphthongs in English, which are: /eɪ/; /ǝʊ/; /aɪ/; /aʊ/; /oɪ/; /ɪǝ/; /eǝ/; /ʊǝ/ (Setyaningsih et al 2019). On the other hand, there are only four diphthongs in Indonesian.…”
Section: The English Diphthongsmentioning
confidence: 99%
“…For example, it was found that Arab learners usually replace some English vowels with another vowel, which can cause embarrassment for the speaker, difficulties for the receiver to comprehend them as these substitutions may result in a change of the meaning in the message delivered. Arab learners often confuse the following vowel contrasts: /e/ versus /ɪ/, /ɒ/ versus /ʊ/, and /ɑ:/ versus /ae/ (Setyaningsih, Wijayanto, & Suparno, 2019). Thus, the words containing these vowels are produced and perceived incorrectly, such as in /tǝn/ is produced and perceived as/tɪn/, /hɑt/ as /hʊt/, and /kɑ:t/ as /kaert/.…”
Section: Introductionmentioning
confidence: 99%